2015
DOI: 10.4103/2277-9175.150388
|View full text |Cite
|
Sign up to set email alerts
|

Geranisetron versus gabapentin in preventing postoperative nausea and vomiting after middle ear surgery in adults: A double-blinded randomized clinical trial study

Abstract: Background:The incidence of postoperative nausea and vomiting (PONV) after middle ear surgery is high. In this study we want to compare the effects of intravenous granisetron and oral gabapentin as a premedication before surgery on the incidence and severity of PONV after middle ear surgery in adult patents.Materials and Methods:We enrolled 90 patients that were randomly divided into the three groups of 30 in each. Group I received granisetron 3 mg iv 2 minutes before induction of anesthesia; Group II received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Behavioural tests were conducted for several days from day 21. The selection of the doses of scopolamine and E. amoenum extract based on previously published studies (Asgharzade et al 2015; Safaeian et al 2015). After behavioural tests, rat underwent general anesthesia using Chloral hydrate (800 mg/kg) and sample of brain tissue was obtained and stored at -70 °C for biochemical assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioural tests were conducted for several days from day 21. The selection of the doses of scopolamine and E. amoenum extract based on previously published studies (Asgharzade et al 2015; Safaeian et al 2015). After behavioural tests, rat underwent general anesthesia using Chloral hydrate (800 mg/kg) and sample of brain tissue was obtained and stored at -70 °C for biochemical assays.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroprotective effects of E. amoenum, including anti-ischemic (Safaeian et al 2015), analgesic (Heidari et al 2006) and anxiolytic effects (Rabbani et al 2004), have been shown in animal models. Recent studies have suggested that the aqueous extract of E. amoenum is effective in treating patients with mild to moderate depression (Asadi et al 2004), as well as obsessive-compulsive disorder (Asadi et al 2004), and generalized anxiety disorder (Sayyah et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of prophylactic gabapentin 600 mg orally reduced the incidence of PONV and antiemetic drug requirements after abdominal hysterectomy [ 22 ]. A study by Heidari et al [ 23 ] comparing the effects of premedication with i.v. granisetron and oral gabapentin on the incidence and severity of PONV after middle ear surgery reported that the efficacy of gabapentin 300 mg in preventing PONV was similar to that of granisetron 3 mg up to 24 h after anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies suggested that using oral gabapentin (an anticonvulsant) before surgery significantly reduced the incidence of postoperative nausea and vomiting after open cholecystectomy. [ 30 33 ] It has been suggested that antiemetic effect of gabapentin is caused by reducing the activity of tachykinin neurotransmitter. [ 2 , 9 ] Furthermore, vitamin B6 has been known to possess antiemetic effects since 1942.…”
Section: Discussionmentioning
confidence: 99%